Perjanjian Perkawinan dalam Upaya Perlindungan Hak-Hak Perempuan - ABD Rouf; Nynda Fatmawati Octarina (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
In a marriage, the aim is to create a happy household, a family filled with peace, love and affection. Marriage causes the mixing of husband and wife's assets or joint assets, unless they make a Marriage Agreement which regulates the separation of assets. A marriage agreement does not only discuss matters of property but also all matters related to the obligations of husband and wife. Prior to the Constitutional Court Decision No. 69/PUU-XIII/2015, marriage agreements could only be made before the marriage occurred. And after the issuance of Constitutional Court Decision No. 69/PUU-XIII/2015, agreements can be made after marriage. The purpose of the marriage agreement is to provide preventive and repressive legal protection, in addition to preventing problems arising in the household such as fighting over property, domestic violence, negligence of rights and obligations between husband and wife. This is a form of protecting women's rights in marriage.